Associations between omega-3 fatty acids, selenium content, and mercury levels in wild-harvested fish from the Dehcho Region, Northwest Territories, Canada. Issue 1 (2nd January 2017) - Reyes, Ellen S.; Aristizabal Henao, Juan J.; Kornobis, Katherine M.; Hanning, Rhona M.; Majowicz, Shannon E.; Liber, Karsten; Stark, Ken D.; Low, George; Swanson, Heidi K.; Laird, Brian D.
ABSTRACT: To better understand the risks and benefits of eating wild-harvested fish from the Northwest Territories, Canada, levels of total mercury (HgT) and selenium (Se) and composition of omega-3 fatty acid ( n -3 FA) were measured in muscle tissue of fish harvested from lakes in the Dehcho Region, Northwest Territories, Canada. Average HgT levels ranged from 0.057 mg/kg (cisco) to 0.551 mg/kg (northern pike), while average n -3 FA concentrations ranged from 101 mg/100 g (burbot) to 1, 689 mg/100 g (lake trout). In contrast to HgT and n -3 FA, mean Se concentrations were relatively similar among species. Consequently, species such as lake whitefish, cisco, and longnose sucker displayed the highest nutrient levels relative to HgT content. Levels of HgT tended to increase with fish size, while Se and n -3 FA levels were typically not associated with fork length or fish weight. Interestingly, HgT concentration was occasionally inversely related to tissue nutrient content. Significant negative correlations were observed between Hg and n -3 FA for lake trout, northern pike, and walleye. There were also significant negative correlations between Hg and Se noted for lake whitefish, cisco, and northern pike. Samples with the highest nutritional content displayed, on occasion, lower levels of HgT. This study provides valuable information for the design of probabilistic models capable of refining public health messaging related to minimizing Hg risks and maximizing nutrient levels in wild-harvested fish in the Canadian subarctic.